Identification of Perinatal Risk Factors for Auditory Neuropathy Spectrum Disorder. (1st July 2020) - West, Alisha N.; Kuan, Edward C.; Peng, Kevin A.
Abstract : Objectives/Hypothesis: To identify medical risk factors associated with auditory neuropathy spectrum disorder (ANSD). Study Design: Retrospective case–control study. Methods: During a 2‐year period (2013–2014) patients with newly diagnosed ANSD were identified at a tertiary care facility. Twenty‐two patients (n = 22) were identified aged 0.5 to 8.1 years. There were 15 males and seven females. Sixteen had bilateral, four had left‐sided, and two had right‐sided ANSD. Two age‐matched, side‐matched, and gender‐matched control groups were then collected. The first group was 22 normal‐hearing children (n = 22). The second was 22 children with sensorineural hearing loss (SNHL) (n = 22) who did not meet the criteria for ANSD. The chart of each subject was reviewed for the following five‐predictor variables: prematurity, low birth weight, jaundice, use of mechanical ventilation, and administration of ototoxic medications. Analysis of variance was performed to analyze the prevalence of perinatal risk factors among the three groups. Multivariate linear regression was then applied. Results: When comparing the ANSD group to both the normal‐hearing and SNHL groups, the subjects with ANSD had statistically significant higher rates of prematurity, low birth weight, jaundice, and mechanical ventilation. Multiple regression analysis was performed to identify predictors of ANSD compared to each control group individually. Jaundice in the first month of life approached significance when comparing the ANSD group to the normal‐hearing group, and was the only medical risk factor found to be statistically significant when comparing the ANSD group to the SNHL group. Conclusions: A history of neonatal hyperbilirubinemia was significantly more common in children with ANSD compared to children with severe SNHL. Level of Evidence: 3 Laryngoscope, 131:671–674, 2021